If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2z + ix = 4 Reorder the terms: ix + 2z = 4 Solving ix + 2z = 4 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-2z' to each side of the equation. ix + 2z + -2z = 4 + -2z Combine like terms: 2z + -2z = 0 ix + 0 = 4 + -2z ix = 4 + -2z Divide each side by 'x'. i = 4x-1 + -2x-1z Simplifying i = 4x-1 + -2x-1z
| 2c+9=15 | | 12k-10=86 | | 13+3(p-3)-5(2-p)=0 | | -10(3p-7q)+50q-30p=0 | | ax+y+1=a-x | | -2(p+3q)-2(6p-7q)=0 | | 7a(1+b)-a(4+b)=0 | | 7a(1+b)-4a(4+b)=0 | | 2x*x=100 | | 11-3(x+5)-6x=0 | | f(x)=2x^2-9x-35 | | 11+25-5=2x-5 | | 5/9x15 | | 25/0.03 | | 5ln(a)-2=0 | | 2a+3b+4a=50 | | sqrt(21x+1)+sqrt(13x-1)=4 | | c=2a+3b+c | | 2(a+b)-5(2a-b)=0 | | -30x+2=-4x^2+5x+11 | | 4(x+3y)+3x=0 | | 2a-4b-a-6b=0 | | x^3-22x^2+73x=-242 | | 2a*-4b-a*-6b=0 | | -15x^2-14=0 | | 3x*(-3)=-9x | | -5x*2y+5y*3x=0 | | x^2+10x-5=-3x^2+2x | | 2*4x-3*3x=0 | | -20=-10r | | 3x^2-20=55 | | G=Q+Qrt |